Influence of the coach's method and leadership profile on the positive development of young players in team sports - de Albuquerque, L. R.; Scheeren, E. M.; Vagetti, G. C.; de Oliveira, V. (Journal of Sports Science & Medicine, 2021)
In a time of instability caused by adolescence, sport may represent a resource to prevent future individual and social problems. Within the complex relationships developed in social sports contexts, the figure of the coach can be fundamental for the development of a beneficial environment. The objective of the research was to investigate the relationship between the teaching methods and leadership profile of the coach and outcomes on the perception of positive development of young people participating in an after school sports program. In total participated, 910 adolescents (14.0 ± 1.8 years) and 57 coaches (45.57 ± 7.25 years) in 37 public schools in the city of Curitiba, in the state of Paraná-Brazil. Ordinal logistic regression was used to verify the independent associations between the variables sex, category, sport, trainer methodology, perception of the coaches, and perception of the athletes with the tertiles of the scores of each developmental characteristic of the young athletes (personal and social skills, cognitive skills, goal setting, and initiative). Odds ratios (OR) were obtained with a 95% confidence interval (95%CI), adopting p < 0.05. The small sized games method were positively associated with cognitive skills and goal setting. Positive associations were also found between athletes` perceptions of the leadership profile of coaches with: personal and social skills (instructor, democratic behaviour, social support, and positive feedback), cognitive skills (instructor, democratic behaviour, and social support), goal setting (instructor, social support, and positive feedback), and initiative (instructor and positive feedback). In addition, the athletes` perception of the coaches` autocratic behaviour was inversely associated with personal and social skills and goal setting. For the evaluated program, the results suggest the choice, on the part of the coaches, of small sized games, combined with a democratic, affective, motivating leadership profile that provides instructions on technical skills and game strategies. The combination of the designated psych-pedagogical aspects is correlated to the positive development of young people through team sports.